Electrochemical Studies of the Inhibition and Activation Effects of Al (III) on the Activity of Bovine Liver Glutamate Dehydrogenase - Shuping Bi; Laifa Li; Xiaodi Yang (Sensors, 2005)
Since the study of Al3+ ion on the enzyme activity by using of electrochemical techniques was rarely found in available literatures, the differential-pulse polarography (DPP) technique was applied to study the effects of Al3+ ion on the glutamate dehydrogenase (GDH) activity in the catalytical reaction of Î±-KG +NADH+NH4 + â L-Glu+NAD++H2O by monitoring the DPP reduction current of NAD+. At the plant and animal physiologically relevant pH values (pH=6.5 and 7.5), the GDH enzyme activities were strongly depended on the concentrations of the metal ion in the assay mixture solutions. In the lower Al (III) concentration solutions (<30 Î¼M), the inhibitory effects were shown, which are in accordance with the recently biological findings. With the increase of Al (III) concentrations (30~80 Î¼M), the enzyme GDH activities were activated. However, once the concentration of Al (III) arrived to near 0.1 mM level (>80Î¼M), the inhibition effects of Al (III) were shown again. The cyclic voltammetry of NAD+ and NAD+-GDH in the presence of Al (III) can help to explain some biological phenomena. According to the differential-pulse polarography and cyclic voltammetry experiments, the present research confirmed that the electrochemical technique is a convenient and reliable sensor for accurate determination of enzyme activity in biological and environmental samples.